Avaliação de biomarcadores de inflamação e de permeabilidade intestinal em adolescentes obesos - Silveira, Cylmara Gargalak Aziz (2020)
INTRODUCTION: The obesity is a pro-inflammatory disease that can also alter the intestinal barrier permeability that contributes to the imbalance of innate and acquired immunity, endothelial lesions and the consequent increased risk of cardiovascular disease. OBJECTIVE: To evaluate inflammatory and intestinal permeability biomarkers in obese adolescents compared to eutrophic adolescents and to evaluate the effect of the symbiotic intervention on such biomarkers in the obese group. METHODS: Prospective clinical study, which were studied 18 obese adolescents and 20 eutrophic adolescents. The following evaluations were carried out: 1) Body composition: bioimpedance (BIA) and BMI; 2) Marker of inflammation: IL6; 3) Evaluation of immune cells: CD4+ T lymphocytes, T reg lymphocytes and monocytes; 4) Intestinal permeability markers: Zonulina and Lipopolysaccharide (LPS). Obese adolescents received the symbiotic Simbioflora® for sixty days and after that were evaluated for the parameters described above. RESULTS: As expected, obese adolescents had a higher fat mass index, less fat-free mass, less dry lean mass and a higher BMI. Obese adolescents showed a significant increase in systolic blood pressure (109±9 vs. 101±9; p: 0,009); insulin (9,6±3,7 vs. 18,9±8,9; p:0,02); triglycerides (71±23 vs. 104±45; p:<0,01); lymphocyte CD4+ (8,9±7,5 vs. 18,0± 12,4; p:<0,01), IL6 (0,26±0,06 vs. 0,30±0,06; p:0,02), and LPS (0,08±0,05 vs. 0,18±0,15; p:<0,01). After intervention with symbiotics in obese adolescents, we observed a significant increase in CD4+ (18,0±12,4 vs. 29,6±10,6; p:0,002) and T reg lymphocytes (9,9±5,4 vs. 14,0±6,7; p:0,02). CONCLUSION: Obese adolescents present a deleterious anthropometric, biochemical and inflammatory changes that may in future contribute to a higher risk of diabetes and cardiovascular outcomes such as hypertension. The increase in serum LPS in this population may indicate the effect of the pathophysiological mechanism of obesity on the breakdown of the intestinal barrier, contributing to a state of microinflammation. Symbiotic supplementation was able to increase expression of T reg lymphocytes; that play anti-inflammatory effect.